Education about Vaginal Birth After Cesarean (VBAC) and Pregnancy Examinations for Pregnant Women - Novelia, Shinta; Carolin, Bunga Tiara (Rajaki of Tulip Medika Publisher, 2024)
Health development aims to increase awareness, ability, and willingness to live a healthy life for every individual, enabling the attainment of the highest possible level of health. In other words, it is expected that the community can play a role as actors in health development by maintaining and improving their own health and actively contributing to the realization of community health. Mothers giving birth through Cesarean Section (CS) have been proven to significantly increase maternal mortality. The risk is higher in planned elective CS deliveries (Villar, 2006). In recent years, the incidence of CS deliveries has exceeded the WHO target. Efforts for Vaginal Birth After Cesarean (VBAC) have relatively low interest (ACOG, 2010). Mothers' fear of undergoing normal delivery is influenced by various factors, including anxiety and lack of knowledge. The objective of this activity is to increase the knowledge of pregnant women about Vaginal Birth After Cesarean (VBAC) and provide prenatal care. The results of the activity show that many pregnant women are enthusiastic about enhancing their knowledge of VBAC. Some pregnant women actively inquire about VBAC and are motivated to follow the procedures. Pregnant women also feel significant benefits from free prenatal examinations.